Comment s’articule l’intervention environnementale avec les pratiques et utopies du développement durable ? L’exemple du Conservatoire du Littoral et de ses partenaires gestionnaires - Jean-Baptiste Narcy; Charlotte Michel; Claire Bouteloup (Développement Durable et Territoires)
While sustainable development has grown inescapable, environmental actors are to produce token of their “sustainability”. This paper analyses how a major actor in the conservation of sites of natural interest in France – namely the Conservatoire du Littoral (CEL) – organises its own intervention in the sustainable development of territories. What visions of the territories and of their socio-economy development does it bring? How does it bridge its environmental action with the sustainable development utopia? Based on several case studies launched by the CEL itself in 2007, the present paper analyses different types of governance and their associated visions of sustainable development. The paper concludes on what are the policy implications of such statements for the CEL.